2019
DOI: 10.1002/fuce.201900022
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Activity of Galvanostatically Deposited Ni Thin Films for Methanol Electrooxidation

Abstract: Nickel and nickel‐based nanomaterials are an attractive choice to replace noble metals as electrocatalysts in alkaline direct alcohol fuel cells (ADAFCs) owing to their lower cost and suitable electrocatalytic activity. Among the different synthetic methods available for the production of nanostructured materials, galvanostatic electrodeposition offers a fast and simple means of fabricating active electrodes. Therefore, thin‐layers of nickel were electrodeposited onto polycrystalline gold electrodes using cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Applying a potential pulse of −1.259 V versus RHE would result in the formation of a 1 to 2 nm thick Ni layer, depending on the Ni 2+ concentration of the platting bath. Recently Salinas‐Quezada et al [25] . showed that galvanostatic electrodeposition on Ni on Au also leads to the formation of Ni thin‐layers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Applying a potential pulse of −1.259 V versus RHE would result in the formation of a 1 to 2 nm thick Ni layer, depending on the Ni 2+ concentration of the platting bath. Recently Salinas‐Quezada et al [25] . showed that galvanostatic electrodeposition on Ni on Au also leads to the formation of Ni thin‐layers.…”
Section: Resultsmentioning
confidence: 99%
“…Our group previously used single-pulse galvanostatic electrodeposition to generate Ni thin-layers on a Au electrode; the Ni deposits exhibit high catalytic activity for methanol electro-oxidation. [25] The same methodology can be used to obtain NiMo deposits with HER activity in acidic media. [26] Herein we report a systematic study on the influence of the applied current density on the PtNi deposit's activity and surface composition for HER in alkaline media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ni-based nanocomposites possess great prospects for practical applications, particularly in water purification processes. Electrochemically deposited Ni nanotubes on various supports been intensively studied, 25 demonstrating their potential in catalytic, 26,27 biomedical 28,29 and sensors 30 applications. The electroless deposition technique has also been applied for synthesis of hollow nickel or nickel oxide nanotube arrays, highlighting their excellent catalytic and conductive properties.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the potential applications of ADMFC, many works have focused on the synthesis of materials with electrocatalytic activity comparable to that of platinum. Salinas et al (6) showed that Ni films deposited on Au under galvanostatic control had a high electrocatalytic activity compared to similar material synthesized by more expensive and time-consuming methods. In this work, Ni films were deposited by the galvanostatic method on polycrystalline gold electrodes.…”
Section: Introductionmentioning
confidence: 99%